The Effects of 20-kDa Human Placental GH in Male and Female GH-deficient Mice: An Improved Human GH? - List, Edward O (Endocrinology, 2020)
A rare 20K isoform of GH-V (here abbreviated as GHv) was discovered in 1998. To date, only 1 research article has characterized this isoform in vivo, observing that GHv treatment in male high-fat fed rats had several GH-like activities, but unlike GH lacked diabetogenic and lactogenic activities and failed to increase IGF-1 or body length. Therefore, the current study was conducted to further characterize the in vivo activities of GHv in a separate species and in a GH-deficient model (GH-/- mice) and with both sexes represented. GHv-treated GH-/- mice had significant increases to serum IGF-1, femur length, body length, body weight, and lean body mass and reduced body fat mass similar to mice receiving GH treatment. GH treatment increased circulating insulin levels and impaired insulin sensitivity; in contrast, both measures were unchanged in GHv-treated mice. Since GHv lacks prolactin receptor (PRLR) binding activity, we tested the ability of GH and GHv to stimulate the proliferation of human cancer cell lines and found that GHv has a decreased proliferative response in cancers with high PRLR. Our findings demonstrate that GHv can stimulate insulin-like growth factor-1 and subsequent longitudinal body growth in GH-deficient mice similar to GH, but unlike GH, GHv promoted growth without inhibiting insulin action and without promoting the growth of PRLR-positive cancers in vitro. Thus, GHv may represent improvements to current GH therapies especially for individuals at risk for metabolic syndrome or PRLR-positive cancers.